In the Interest of Privacy, Some Names Have Been Changed: Rewriting and Richardson's Pamela - Milne, Anne (My University, 1994)
This study examines the issue of rewriting, its impact on Samuel Richardson's editorial and writing practice and the implications this practice has had for women. Using Richardson's 1741 novel, Pamela, as the example, the study focuses in its first chapter on the circumstances surrounding Richardson's creation of a sequel (Pamela II) to the enormously successful two-volume Pamela I.
In Chapter two, three rape scenes are closely read for the ways in which they are rewritten or retold by various characters and across the gap between "original" version and sequel. The pattern which emerges is one of increasing editorial control of Pamela's writing by her husband. Pamela is also shown to be complicit in this rewriting process.
In Chapter three, the author of this study enters into the rewriting process herself in order to explore the relationship between circumscribed women's roles in the Eighteenth Century and the situation for women today. This issue is explored through the use of feminist and psychoanalytic theory as well as contemporary media imagery.
[missing page 37]
Keywords: English; English Language and Literature; English Language and Literature